2006
DOI: 10.1111/j.1745-7599.2006.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery embolization as a treatment for symptomatic uterine fibroids: A review of literature and case report

Abstract: The NP is instrumental in identifying which patients may be appropriate candidates for UAE, educating them about the risks and benefits of the procedure, and managing these patients before and after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Previously, some studies have shown that uterine arteries blocked by UAE may reduce blood supply to the ovaries, which may further influence the ovarian function and subsequent fertility. There were reports in the literature regarding adverse events associated with performing UAE for fibroids, including endometrial atrophy and ovarian failure 24. Besides, patients receiving UAE were also at a risk of secondary and uncontrolled vaginal bleeding, which may lead to inevitable hysterectomy 25.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, some studies have shown that uterine arteries blocked by UAE may reduce blood supply to the ovaries, which may further influence the ovarian function and subsequent fertility. There were reports in the literature regarding adverse events associated with performing UAE for fibroids, including endometrial atrophy and ovarian failure 24. Besides, patients receiving UAE were also at a risk of secondary and uncontrolled vaginal bleeding, which may lead to inevitable hysterectomy 25.…”
Section: Discussionmentioning
confidence: 99%
“…UAE is a minimally invasive, image-guided therapy, in which the blood supply to the uterine fibroid is blocked by catheterization, and the ischemic necrosis of the fibroids is induced by the insertion of embolic particles [13]. The embolic particles are usually composed of polyvinyl alcohol, tris-acryl, or gelatin sponge material.…”
Section: Introductionmentioning
confidence: 99%